Flux conservation, radial scalings, Mach numbers, and critical distances in the solar wind: magnetohydrodynamics and Ulysses observations. Issue 4 (19th July 2021) - Verscharen, Daniel; Bale, Stuart D; Velli, Marco
ABSTRACT: One of the key challenges in solar and heliospheric physics is to understand the acceleration of the solar wind. As a super-sonic, super-Alfvénic plasma flow, the solar wind carries mass, momentum, energy, and angular momentum from the Sun into interplanetary space. We present a framework based on two-fluid magnetohydrodynamics to estimate the flux of these quantities based on spacecraft data independent of the heliocentric distance of the location of measurement. Applying this method to the Ulysses data set allows us to study the dependence of these fluxes on heliolatitude and solar cycle. The use of scaling laws provides us with the heliolatitudinal dependence and the solar-cycle dependence of the scaled Alfvénic and sonic Mach numbers as well as the Alfvén and sonic critical radii. Moreover, we estimate the distance at which the local thermal pressure and the local energy density in the magnetic field balance. These results serve as predictions for observations with Parker Solar Probe, which currently explores the very inner heliosphere, and Solar Orbiter, which will measure the solar wind outside the plane of the ecliptic in the inner heliosphere during the course of the mission.